Material Deprivation: a Case of Latvia - Sloka, Biruta; Čīpane, Kate (Klaipeda University, 2019)
Material deprivation has recently gained prominence as a topic of debate as its proliferation is raising throughout Europe in particular in the countries hit hardest by financial and economic turbulences what leads to the gap in material deprivation levels throughout Europe. The aim of the study is to analyze material deprivation in the regions of Latvia. Research methods used in preparation of the paper: scientific publication and previous conducted research results analysis, analysis of anonimised data of EU-SILC survey results and European Central Bank conducted survey on Household income and expenses survey results, results are compared with the results of other EU countries. Survey anonimised data are analyzed using indicators of descriptive statistics, cross-tabulations for regions of Latvia, for urban-rural living and analysis of variance – ANOVA are used. The results of analysis have indicated in what situation are regions of Latvia in the context of material deprivation especially in Latgale region and what are the challenges for decision makers to deal with – more attention for several approaches in reduction of income differences in regions of Latvia.
Keywords: material deprivation; regional development; EU-SILC; Latvia; Research Subject Categories::SOCIAL SCIENCES::Business and economics